Home Sweet Home: New Insights Into the Location of Equine Premises in France and Keeping Habits to Inform Health Prevention and Disease Surveillance - Farchati, Halifa; Merlin, Aurelie; Saussac, Mathilde; Dornier, Xavier; Dhollande, Mathilde; Garon, David; Tapprest, Jackie; Sala, Carole (Frontiers in Veterinary Science, 2021)
Identifying and tracking equines are key activities in equine health prevention. France is one of the few European countries with an operational centralized database that records information on equines, owners and keepers but not on the location and keeping conditions of equines. The objective of our study was to collect information on keeping habits of equines, and the relative location of a wide range of equines, owners and keepers, and discuss their implication for surveillance and control of outbreaks improvement. A national e-mailing survey was conducted among the 1.9% of persons registered as owners and and 8.2% of persons registered as keepers in the French national equine identification database and having given their agreement to be contacted by email. It led to the collection of information from 728 owners, 121 keepers and 2,669 owner-keepers. Most of them housed their equines in a single commune (smallest geographic administrative unit in France), at their home as private individuals. The distance between the communes of residence and of holding was, in most cases (79% of owners in owner survey, 89.5% of the keepers in keeper survey, and about 94 % of the owner-keeper in both survey), less than 30 km. More than half of the keepers kept a maximum of five equines and the majority with two different use/destination together, mostly leisure-retirement, leisure-breeding, leisure-sport, and sport-breeding. The main limitation of the study was that a relatively limited number of people (n=3,518) were reachable due to the low availability of an email address and contact agreement. Nonetheless, the findings provide an overview of how equines are kept by non-professional owners/keepers, and complement information usually collected by the French riding institute. Additionally, information collected would be very helpful to determine a realistic estimate of the spatial distribution of equines in France. This information is very important for the the equine sector, for demographic knowledge but also improvement of surveillance plans and control measures and for the management and monitoring of health events, to limit the spread of diseases.